Gut Microbiota Dysbiosis Drives and Implies Novel Therapeutic Strategies for Diabetes Mellitus and Related Metabolic Diseases - Li, Xuan; Watanabe, Keita; Kimura, Ikuo (Frontiers in Immunology, 2017)
Accumulating evidence over the past decade has linked the development of metabolic syndrome related to diabetes to variations in gut microbiota, an emerging, critical homeostatic regulator of host energy metabolism and immune responses. Mechanistic studies in rodent models have revealed an ever-increasing multitude of molecular mechanisms whereby the gut microbiota interacts with a variety of host sensing and signaling pathways, leading to modulation of endocrine system, immune responses, nervous system activity, and hence, the predisposition to metabolic diseases. Remarkably, the microbiota-driven immune responses in metabolic tissues and the host nutrient-sensing mechanisms of gut microbial metabolites, in particular short-chain fatty acids (SCFAs), have been significantly associated with the proneness to diabetes and related disorders. This review will synthesize the recent efforts on unraveling the mediating role of gut microbiota in the pathogenesis of metabolic diseases, aiming to reveal new therapeutic opportunities.